A novel method for the synthesis of Indolo[2,1-a]isoquinolines and modelling studies of 3-substituted oxindoles against PfPK5 - Sello, Thato Saoeni (My University, 2008)
Many naturally occurring and synthetically made azapolycyclic aromatic ring systems display important biological activities. One class of naturally occurring azapolycyclic aromatic ring systems is the dibenzopyrrocoline alkaloids, made from an indole nucleus fused to an isoquinoline system sharing the same nitrogen, i.e. the indolo[2,1-a]isoquinoline nucleus. The indolo[2,1-a]isoquinoline and its analogues have been reported to possess antileukemic, tubulin polymerization inhibitory and antitumor activity. A variety of indolo[2,1-a]isoquinolines have been synthesized in our labs. This includes, the 5,12-dimethyl-6-phenylindolo[2,1-a]isoquinoline, using the Suzuki- Miyaura cross-coupling reaction and reaction conditions for the formation of aromatic rings (KOBut in DMF) developed in our laboratories. In this dissertation, we outline the syntheses of (±)-5,6-dihydro-6-phenylindolo[2,1-a]isoquinolin-5-ol and 2-(1-benzyl-1H-benzo[d]imidazol-2-yl)benzaldehyde. We also discuss the synthesis and the modelling studies, (docked in silico) of the 3-substituted oxindoles in the X-ray crystal structure of the PfPK5 cyclin dependent kinase (CDK). The synthesis of indolo[2,1-a]isoquinolines started with N-protection of isatin and benzimidazole with a benzyl group to afford 1-benzylindoline-2,3-dione and 1- benzyl-1H-benzo[d]imidazole, respectively. The next step was the synthesis of the brominated compound, 1-benzyl-2-bromo-1H-indole, and the iodated compound, 1-benzyl-2-iodo-1H-benzo[d]imidazole. 1-Benzyl-2-bromo-1H-indole was synthesized by means of a functional group interconversion of the oxygen in the 3-position of isatin to two chlorine atoms initially, followed by removal of those chlorine atoms with activated zinc, followed by the conversion of the carbonyl of the oxindole to give a 2-bromoindole using POBr3. 1-Benzyl-2-iodo-1Hbenzo[ d]imidazole was synthesized in two ways. Firstly, 1-benzyl-1Hbenzo[ d]imidazole was exposed to LDA followed by iodinating the 2-position by 5 exposure of the intermediate to diiodoethane. The second method uses a halogenating method developed in our labs. 1-Benzyl-1H-benzo[d]imidazole was exposed to isopropylmagnesium chloride lithium chloride followed by I2. Having obtained the halogenated products, both sets of halogenated precursors were coupled with 2-formylphenylboronic acid using the Suzuki-Miyaura crosscoupling reaction to obtain the products, 2-(1-benzyl-1H-indol-2-yl)benzaldehyde and 2-(1-benzyl-1H-benzo[d]imidazol-2-yl)benzaldehyde in 98 and 67% yield, respectively. Aromatization of 2-(1-benzyl-1H-indol-2-yl)benzaldehyde occurred easily using tBuOK in DMF at room temperature to afford (±)-5,6-dihydro-6- phenylindolo[2,1-a]isoquinolin-5-ol in 75% yield (7:3 ratio of anti-: syn-) but exposing 2-(1-benzyl-1H-benzo[d]imidazol-2-yl)benzaldehyde to the same reaction conditions did not afford the desired product. Dehydrating (±)-5,6- dihydro-6-phenylindolo[2,1-a]isoquinolin-5-ol using methanesulfonyl chloride in CH2Cl2 was unsuccessful. Further attempts at dehydrating (±)-5,6-dihydro-6- phenylindolo[2,1-a]isoquinolin-5-ol were prevented due to time constraints. In the last part of the project, a library of 3-substituted oxindoles (13 molecules) was synthesized successfully and the compounds were docked in silico in the active site of an X-ray crystal structure of PfPK5, a cyclin dependent kinase of the Plasmodium falciparum, the agent causing the most severe form of human malaria. Eleven of the thirteen compounds were synthesized by condensation of oxindole and a suitable aldehyde in the presence of piperidine. The other two, 3- (propan-2-ylidene)indolin-2-one and 5,6-dimethoxy-3-(methylthio)indolin-2-one, were synthesized differently. 3-(Propan-2-ylidene)indolin-2-one was synthesized by reacting the oxindole with acetone in the presence of HCl and 5,6-dimethoxy- 3-(methylthio)indolin-2-one was synthesized following Gassman’s methodology. Two molecules scored well in the molecular modelling studies using the X-ray crystal structure of PfPK5, namely, (E/Z)-3-(3,4-dimethoxybenzylidene)indolin-2- one and (Z)-3-(4-hydroxybenzylidene)indolin-2-one. 6 In conclusion, we managed to synthesize (±)-5,6-dihydro-6-phenylindolo[2,1- a]isoquinolin-5-ol using the Suzuki Miyaura cross-coupling reaction and reaction conditions that lead to aromatization (tBuOK in DMF at room temperature) as key steps and 2-(1-benzyl-1H-benzo[d]imidazol-2-yl)benzaldehyde using the Suzuki- Miyaura cross-coupling reaction. A library of 3-substituted oxindoles was made and using molecular modelling were docked in silico into the crystal structure of the active site of PfPK5 with 2 compounds showing promise, for further studies.
Keywords: Alkaloids; Indole Alkaloids; Isoquinoline